Institutional Development and Efficiency of Fishermen Co- operatives in Marine Fisheries: A Case Study from Kerala - P. Jeyanthi; V. Chandrasekar; Arathy Ashok; V. Radhakrishnan Nair; K. Jesy Thomas; K. D. Jos and Nikita Gopal (Fishery Technology, 2018)
Fishermen co-operatives have played a significant role in improving the livelihood of millions of fishermen. The extended co-operative services and efficiency of co-operatives over the years make the co-operatives effective. This paper presents the institutional development and efficiency of two fishermen co-operative societies viz., Njarakkal (Society I) and Manassery (Society II) in Ernakulam district, Kerala. It was revealed that there were spatial and temporal differences in institutional development between two societies while delivering co-operative services. From the results of Data Envelopment Analysis (DEA), it was found that the mean technical efficiencies estimated using Variable Returns to Scale (VRS) were 96 and 87% in Society I in and Society II respectively. The scale efficiency revealed that the Society II is operating at sub-optimal scale size than Society I. The amount of loan disbursed and repayment, income from fish marketing services were the factors responsible for the efficiency of co-operatives.